Physical and virtual global food reserves to protect the poor and prevent market failure - von Braun, Joachim; Torero, Máximo (International Food Policy Research Institute, 2008)
The current food crisis has several causes—rising demand for food and feed, biofuels, high oil prices, climate change, stagnant agricultural productivity growth—but there is increasing evidence that the crisis is being made worse by the malfunctioning of world grain markets. Given the thinness of major markets for cereals, the restrictions on grain exports imposed by dozens of countries have resulted in additional price increases. A number of countries have adopted retail price controls, creating perverse incentives for producers. Speculative bubbles have built up, and the gap between cash and futures prices has risen, stimulating overregulation in some countries and causing some commodity exchanges in Africa and Asia to halt grain futures trading. Some food aid donors have defaulted on food aid contracts. The World Food Programme (WFP) has had difficulty getting quick access to grain for its humanitarian operations. Developing countries are urgently rebuilding their national stocks and re-examining the “merits” of self-sufficiency policies for food security despite high costs. These reactions began as consequences, not causes, of the price crisis, but they exacerbate the crisis and increase the risks posed by high prices. By creating a feedback loop with high food prices, they further increase price levels and volatility, with adverse consequences for the poor and for long-term incentives for agricultural production. Because they impede the free flow of food to where it is most needed and undermine the flow of price signals to farmers, these market failures impose enormous efficiency losses on the global food system, hitting the poorest countries and people hardest.